Studies on Germination and Seedling Growth of Neobalanocarpus Heimii (King) Ashton - Zainudin, Siti Rubiah (1990)
Neobalanocarpus heimii (King) Ashton locally known as chengal is endemic to Southern Thailand and Peninsular Malaysia. It is an important genera as it produces wood that has become the standard by which many others are compared. It is fairly widely distributed but found in scattered occurrence and at low numbers. This project focuses on the germination, seedling growth, presence of mycorrhiza and photosynthetic rates under different light conditions. Soil analysis and field observation of seedling distribution around the parent tree were also conducted. Germination of chengal was more rapid at lower light intensities than at higher light intensities. The germination percentage is also influenced by seed size i.e., the bigger the seed the better the germination. Treatment means for plant height and leaves showed no significant difference among treatments. However, the number of nodes was significant in all treatments.